1993
DOI: 10.1071/wr9930387
|View full text |Cite
|
Sign up to set email alerts
|

Home-range estimates and habitat of the yellow-bellied glider (Petaurus australis) at Waratah Creek, New South Wales

Abstract: The yellow-bellied glider (Petaurus australis), the largest of the exudivorous marsupials, lives in small family groupings and occupies virtually exclusive home ranges. A variety of estimation techniques were used to determine the home-range area of five glider groups. Two sets of data were analysed for each glider group; one included the locations of all observations while the other utilised a subset considered to represent independent observations based on a 3-h interval between consecutive locations. The te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 39 publications
0
40
0
Order By: Relevance
“…This facilitated individual recognition when gliders were located at night (Goldingay 1992;Goldingay and Kavanagh 1993). Gliders were weighed, assigned to age classes using tooth condition and ventral fur color, and sex was determined (Quin 1995;Sharpe 2004;Suckling 1984;van der Ree 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This facilitated individual recognition when gliders were located at night (Goldingay 1992;Goldingay and Kavanagh 1993). Gliders were weighed, assigned to age classes using tooth condition and ventral fur color, and sex was determined (Quin 1995;Sharpe 2004;Suckling 1984;van der Ree 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have found that gliding mammals occupy home-range areas much larger than predicted based on their body mass (Fridell and Litvaitis 1991;Goldingay and Kavanagh 1993;Hanski et al 2000;Jackson 2000;Menzel et al 2006;Witt 1992). The generality of this, or whether it relates to gliding locomotion, is unknown, but if the pattern persists the underlying cause should be of ecological interest.…”
mentioning
confidence: 99%
“…The data were collected over a short period (35 days), involved only one animal of each sex and only one locality. Furthermore, the data sets used to calculate home ranges contained fewer than 100 points; Goldingay & Kavanagh (1993) showed that such small data sets (less than 100 points) for Yellowbellied Gliders tended to under-estimate home ranges.…”
Section: Resultsmentioning
confidence: 99%
“…This is desirable because it facilitates comparison among studies (Harris et al 1990;Goldingay and Kavanagh 1993). Home-range areas have been reported for locations broadly across the geographic range of the koala (Table 3).…”
Section: Home-range Estimatesmentioning
confidence: 99%
“…1). Conducting a compositional analysis such as this is valuable to identify those habitats of key importance, the amounts apparently required and those habitats of lower or no value (see Goldingay and Kavanagh 1993;Sharpe and Goldingay 2007).…”
Section: Home-range Estimatesmentioning
confidence: 99%